Menolak Suap, Menjaga Integritas: Tanggung Jawab Setiap Profesional - Nayla Jasmine Sabrina; Shelma Anrika Dwiyanti (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Bribery is a serious threat to integrity and professional ethics across various fields of work. This article discusses the importance of rejecting bribery as a demonstration of commitment to professional integrity. Using a qualitative approach through literature review and case analysis, this paper highlights how integrity serves as a core pillar in maintaining public trust, promoting transparency, and strengthening work ethics. Every professional bears a moral and legal responsibility to refuse any form of bribery and to foster a clean, high-integrity work culture. The article also offers prevention strategies and ways to instill integrity values in professional environments as concrete steps toward positive change.